Humeral Head Ossification Predicts Peak Height Velocity Timing and Percentage of Growth Remaining in Children. Issue 9 (October 2018) - Li, Don T.; Cui, Jonathan J.; DeVries, Stephen; Nicholson, Allen D.; Li, Eric; Petit, Logan; Kahan, Joseph B.; Sanders, James O.; Liu, Raymond W.; Cooperman, Daniel R.; Smith, Brian G.
Abstract : Background: Understanding skeletal maturity is important in the management of idiopathic scoliosis. Iliac apophysis, triradiate cartilage, hand, and calcaneal ossification patterns have previously been described to assess both peak height velocity (PHV) and percent growth remaining; however, these markers may not be present on standard spine radiographs. The purpose of this study was to describe a novel maturity assessment method based on proximal humeral epiphyseal ossification patterns. Methods: Ninety-four children were followed at least annually throughout growth with serial radiographs and physical examinations. The PHV of each child was determined by measuring the change in height observed at each visit and adjusting for the interval between visits. Percent growth remaining was determined by comparing current to final standing height. The humeral head periphyseal ossification was grouped into stages by 8 investigators ranging from medical student to attending surgeon. Results: The morphologic changes involving the proximal humeral physis were categorized into 5 stages based on development of the humeral head epiphysis and fusion of the lateral margin of the physis. Our novel classification scheme was well distributed around the PHV and reliably correlated with age of peak growth and percent growth remaining with >70% nonoverlapping interquartile ranges. Furthermore, the scheme was extremely reliable with intraclass correlation coefficients of 0.96 and 0.95 for intraobserver and interobserver comparisons, respectively. Conclusions: The humeral head classification system described here was strongly correlated with age of PHV as well as percentage growth remaining. Furthermore, the staging system was extremely reliable in both interobserver and intraobserver correlations suggesting that it can be easily generalized. Clinical Relevance: As a view of the humeral head is almost always present on standard scoliosis spine x-ray at our institution, our classification can be easily adapted by surgeons to gain additional insight into skeletal maturity of patients with scoliosis. We believe that our method will significantly improve the evaluation of the child with scoliosis without increasing radiation exposure, time, or cost.